Style Shifting In A Workplace: A Case Study of Interactions between Superiors and Subordinates in a Private Corporation Company in Bandung - Euis Rina Mulyani; Iwa Lukmana (English Department - University of Sultan Ageng Tirtayasa, 2019)
In Indonesian culture, people vary their way of communicating according to whom they speak to. The addressee’s social attribute, such as age, position, social status, and power, commonly lead the speakers to choose a certain variation of utterances. In other words, style shifting often happens during communication with people of different social factors. The present study concerns style shifting in a workplace between employees of superiors and subordinates position in a private corporation company. This study is aimed at (1) investigating whether the employees at a private corporation company shift their style of speech when communicating with their superiors and subordinates, and (2) the characteristics of their style shifting (if they do). The respondents of this study were 20 workers of the company. They were selected purposefully, male and female workers who had both superiors and subordinates. Questionnaire was employed for the data collection. Both qualitative and quantitative procedures were used to analyze the data. The conclusion of this study is that style shifting is principally influenced by power relation, as shown in use of address terms, apologetic words, length of utterances, directness/indirectness, and formality of expression. Keywords: style shifting; interaction; superior; subordinate